SOSIALISASI INOVASI PRODUK KAYA GIZI DARI HASIL PEMANFAATAN LIMBAH BAHAN PANGAN - Desti Ambar Wati (Jurnal Pengabdian Kepada Masyarakat Ungu( ABDI KE UNGU), 2023)
Food waste is still a problem in Indonesia. This is caused by the limited knowledge of the community about the benefits of food waste from a nutritional and health perspective. Food waste such as jackfruit seeds, banana peels, corn silk, avocado seeds, dragon fruit peels, tofu dregs, shells and shrimp heads also have a high enough nutritional content that they are beneficial to health. The purpose of this socialization is to provide knowledge to the public regarding the benefits of food waste in terms of nutritional aspects with the hope that it can be developed by the community. This activity was carried out during the 2023 Anniversary of Aisyah Pringsewu University by involving 35 students in the 4th semester of the Undergraduate Nutrition Study Program who were divided into 10 groups. The processing methods for food waste products are drying, roasting and frying. Products produced from food waste processing are Dragon Fruit Skin Pie, Malted Flakes (Jackfruit seed Cookies flakes, Colitis (Banana Skin Cookies), Sikju (Shrimp Skin Cheese Sticks), Dolas (Taro Flour Donuts), Crepe Mille Silk Cheese (hair flour) corn), Snackbar Upasta (Purple Sweet Potato and Tofu Dregs), Chumer (Red Bean Churros), Nastar Tekajawo (Nastar Green Bean Flour), Avocado Seeds Cookies (Avocado seed cookies).